Outcomes of laparoscopic colorectal cancer surgery in a non‐metropolitan Australian hospital: audit of 120 patients with long‐term follow‐up results. Issue 12 (10th August 2022) - Wichmann, Matthias W.; McCullough, Timothy K.; Beukes, Eben; Gunning, Thomas; Maddern, Guy J.
Abstract: Background: Laparoscopic colorectal cancer surgery has been shown to produce comparable oncological long‐term results as well as improved short‐term outcomes compared to open surgery in multicentre trials. Limited information is available whether these results are reproduced in non‐metropolitan surgery. Methods: Audit of prospectively collected follow‐up data in a rural surgical centre in South Australia. Short‐ and long‐term results of colorectal cancer patients undergoing elective laparoscopic surgery for cure. Outcomes are compared with results of open surgery. Results: Survival and clinical data of 120 patients after laparoscopic resection were analysed and then benchmarked against results of 157 open resections. Conversion rate was 10.8% ( N = 13). Mean patient age was 69.9 years. Mean number of lymph nodes analysed was 15.5. Mean follow‐up is 53.0 months. Thirty‐day mortality was 0.36% ( n = 1) and 90‐day mortality was 0.72% ( n = 2). No differences in complications rates, long term survival or procedures performed were observed. This is a single centre audit of clinical and oncological outcomes and a number of exclusion criteria were applied. Patient gender, cancer stages as well as number of patients undergoing neoadjuvant radio‐chemotherapy differ significantly between the study and the benchmarking group. Patients were not randomized and the benchmarking group is in part a historical control. Conclusions: This audit of clinical outcomes and survival after laparoscopic CRC resection for cure indicates that minimal invasive surgery may be suitable for adequately staffed and equipped rural centres. Abstract : This is an audit of clinical and oncological outcomes of 120 laparoscopic colorectal cancer resections benchmarked against 157 open resections. The audit indicates that laparoscopic colorectal cancer surgery may be suitable for an adequately staffed and equipped rural centre.